Pembiasaan budaya karakter 5S (Seiri,Seiton,Seiso,Seiketsu, Shitsuke) melalui konseling kelompok teknik modeling untuk meningkatkan kedisiplinan siswa - Yashinta Rizki Ananda; Erny Tri Handayani (Ikatan Bimbingan dan Konseling Sekolah)
Nation character education is increasingly faded due to the indifference of the next generation of the nation in establishing themselves into dignified personalities, this is due to the indiscipline habits. Counseling group of modeling techniques is implemented as a step to form learners to be a person of character and dignity by the habituation of the application of 5S work culture (Seiri (Seat), Seiton (Susun), Seiso (Bersih), Seiketsu (Caring, Hygiene), Shitsuke (Discipline)). This idea is the development of the implementation of the 5S program which is still found by students who are not disciplined. This study aims to improve student discipline by familiarizing the 5S culture through group technique modeling counseling. Grouping technique counseling is conducted through heterogeneous and closed groups. Group members are selected by counselors based on student discipline levels from high to low. The model used is a model directly or symbolically by displaying profiles of people who are successful and successfully apply the 5S culture. Through this activity is expected to increase student discipline to become a person of character and dignity.